(untitled) (Communications in Computational Physics, 2008)
Recent years have witnessed significant improvement in implicit solvents based on the Poisson-Boltzmann theory, whether in the forms of numerical solution or analytical approximation. Especially worth noting are the improvements and revisions of those implicit solvents for stable dynamics simulations. Given these technical advancements, attentions are now paid to the quality of implicit solvents as compared with the more expensive explicit solvents. The new developments in nonpolar solvents mentioned above and reviewed elsewhere will also result in more accurate simulations of biomolecules. We have also touched the new challenges facing the implicit solvents. That is how to incorporate these solvents in the emerging polarizable force fields. New challenges could also arise from the assumptions underlying all implicit solvents, as recently explored to couple electrostatic and nonelectrostatic components together. In addition, hybrid solvents could eventually become a reality for dynamics simulation even this has been proposed in the early days of computational biochemistry. It is likely that such hybrid solvents will offer the necessary accuracy, as they no longer average out the very degrees of freedom that are of interest in studies where solute/solvent coupling is crucial.